Representasi Kekuasaan Dan Kekerasan Dalam Film Bitch X Rich - Tria Dewi Putri; Eni Murdiati; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The movie Bitch X Rich is a short Korean drama about the life of Cheongdam International High School students. The lives of these high school students become compartmentalized, only because of differences in economic and social status. The movie Bitch X Rich unwittingly turns out that there are also many negative things happening in the film. Thus there are several scenes that are quite disturbing and uncomfortable to watch such as power and verbal and non-verbal violence. The problem in this study is how the elements of power and violence contained in the movie Bitch X Rich according to Roland Barthes semiotics seen from denotation, connotation and myth. This research uses descriptive methods and uses a qualitative approach. The results revealed that in the movie Bitch X Rich there are scenes of power and verbal and non-verbal violence. Power is the ability to influence others to think and behave according to the will of the influencer. Verbal violence is a form of violence characterized by speech in this film, In the film Bitch X Rich, four findings of power representation were found. First, the depiction of acts of power from Seo Hee Soo who tried to eliminate traces of murder. Second, the act of power from Baek Je Na. Third, the act of power from Kang Na Yeon's mother who wants to destroy Kim Hye In's life. And finally, acts of power from the highest education project students who bully the equivalent education project students. Then, in the findings of physical violence, there were scenes of beating and murder committed by Yul Hee to Kim Hae In. In addition, there are also scenes of beatings and torture committed by Kim Hye In to Baek Je Na. While in non-physical violence, there are threats and accusations made by Kim Hye In to Baek Je Na. There were also physical and non-physical forms of violence committed by Kang Na Yeon's mother to Kim Hye In. Finally, there were acts of beating and torture committed by Si Eun to other students. In non-physical violence, threats, insults, and harassment committed by students to other students were found. This verbal violence can affect various aspects of life, such as academic performance and social relationships. Overall, the representation of power and violence in the film Bitch X Rich is dominated by physical violence shown through actions, conflicts, and character dialog. This is also in line with the theory of violence used in this study, that violence is used in entertainment to attract audiences.